Effects of chlorhexidine and gaseous ozone on microleakage and on the bond strength of dentin bonding agents with compomer restoration on primary teeth - Arife Kapdan; Nurhan Öztaş (Elsevier, 2015)
Background/purpose: The aim of this study was to evaluate microleakage and bond strength in primary tooth dentin after disinfection with chlorhexidine solution or gaseous ozone. Materials and methods: Sixty primary first and second molar teeth without caries were collected. Thirty of these teeth were ground to expose the dentin surface and divided into three groups (n = 10 for each group). After the application of materials, the teeth were restored with compomer restorations. Dentin sticks were obtained from these specimens and used for the microtensile bond strength test. The effect on the microleakage of the same materials of compomer restorations was then tested. class V cavities were prepared on the facial surfaces of the remaining 30 sound primary first and second molars to which the materials were applied and that were restored with compomer. The teeth were thermocycled, stained with basic fuchsine, sectioned for microleakage evaluation, and examined under a stereomicroscope. Kruskall-Wallis, Mann-Whitney U, one-way ANOVA, and post hoc Tukey tests were used for statistical analyses. Results: When the bond strength of the groups were compared, the difference between the ozone group and the control group was not significant (P > 0.05); however, the difference between the chlorhexidine group and either of the other two groups was significant (P < 0.05). The chlorhexidine group of teeth showed the lowest bond strength rates. When the occlusal and gingival microleakage rates among the groups were compared, the difference was insignificant (P > 0.05). Conclusion: Ozone application may be an alternative antibacterial procedure because the bond strength increased after ozone application. Chlorhexidine decreased bonding significantly. There was no significant difference between the microleakage values.